Evidence for Whistler Waves Propagating Into the Electron Diffusion Region of Collisionless Magnetic Reconnection. Issue 7 (9th April 2022) - Zhong, Z. H.; Zhou, M.; Graham, D. B.; Khotyaintsev, Yu. V.; Wu, Y. F.; Le Contel, O.; Li, H. M.; Tao, X.; Tang, R. X.; Deng, X. H.
Abstract: Despite a growing number of observations of whistler waves in/around the reconnection diffusion region, the origin of the whistler waves in the diffusion region and their role in reconnection remain elusive. This paper investigates the whistler‐mode waves within an electron‐scale reconnecting current sheet observed by the Magnetospheric Multiscale mission on 23 December 2016. These whistlers were observed in both the electron diffusion region (EDR) and the immediate inflow region of the electron‐scale magnetic reconnection site. The dispersion relation of these whistlers is measured and compared to predictions from linear theory for the first time in these regions. The comparison shows that the field‐aligned drifting electron component critically modifies the dispersion relation of whistlers in the EDR due to the Doppler‐shift effects. We demonstrate that these whistlers propagated into the EDR from outside rather than locally excited, however, they did not provide sufficiently large anomalous dissipation in this EDR. Plain Language Summary: Whistler‐mode waves are important plasma waves in the space plasma system, which can effectively interact with electrons to exchange energy. Whistler waves are frequently observed in various areas of magnetic reconnection, for example, outflow region, separatrix region, and diffusion region. However, the nature of whistler waves in the electron diffusion region (EDR), where the magnetic field line is broken and reconnected, is still unclear. Here, we present an observation of whistler waves in the EDR and the inflow region of magnetic reconnection. These whistler waves originate from the outside and propagate into the vicinity of the reconnection site. We measured the dispersion relation of these whistler waves for the first time within these regions and compare it with the dispersion relations predicted by linear theory. The results indicate that the effects from the drift velocity of electrons play a key role in modifying the dispersion relation of these whistlers in the EDR. Additionally, we find that these whistlers did not provide effective anomalous dissipation in this EDR. These results advance our knowledge of the source and features of whistlers in the vicinity of the reconnection site. Key Points: Observations confirm that whistler waves can propagate into the electron diffusion region (EDR) from outside The dispersion relation of the whistler waves is measured for the first time in the EDR The observed whistler waves contributed to negligible anomalous effects in the EDR